Perceptions of Internet Marketing Effectiveness within the South African FMCG Retail Sector - Vandayar, Vilashni (My University, 2012)
Technology is changing the face of the retail-shopping environment, with many industries adopting online services to either replace or supplement their traditionally “brick and mortar” businesses. The phenomenal growth of the Internet has changed the way business is conducted from the traditional bricks and mortar model and has brought about huge opportunities for both the business and the consumer. Given the profound impact the Internet is having on the way business is conducted, most traditional businesses today have an online presence. Prior research found that although internationally many companies use the Internet as part of their integrated marketing campaigns, the most popular uses of the Internet were product and company information, communication to consumers, and customer service. The purpose of this research was to to evaluate the perceived effectiveness of Internet marketing within the FMCG retail sector in South Africa as an integrated marketing channel. It was found that South African FMCG retailers are using the Internet for the same purposes as international retailers. It was also concluded that South African FMCG retailers do not believe that they are using the Internet to its full potential in terms of being a transactional medium. This is a conscious decision of the retailers, as they believe that the Internet should be used on a more strategic level to engage with their target audience in real time rather than an alternate distribution channel.
MBA thesis - WBS
Keywords: Internet marketing; Marketing; Retail industry